“SHINING WITH SOUND IN THE UNTRANSLATABLE DARK”—REBECCA ELSON’S POETRY OF COSMIC WISDOM - More, Octavian (Studia Universitatis Babeș-Bolyai. Philologia, 2024)
“Shining with sound in the untranslatable dark”—Rebecca Elson’s Poetry of Cosmic Wisdom. Despite having left us only a small body of verse, collected in the posthumously published A Responsibility to Awe (2001), Montreal-born astrophysicist and poet Rebecca Elson impresses through a particular sensibility resulting from the unlikely union of positivist certitude and existential angst informed by an acute sense of one’s biological finitude. In this paper, intended both as a recuperative effort and an interpretive exercise, we will try to shed light on how poetry, as Elson’s case demonstrates, can be a fundamentally ecological effort and a disciplined quest for belonging, reminding us that even the most unremarkable aspects of our everyday existence are irrevocably linked to our profound connections with the universe.